Effectiveness of Employee Additional Income towards Employee’s Performances: A Study on Department of Employment, Administration and Public Services in Secretariat of The Administrative City of East Jakarta (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2022)
The objectivef the research was to analyze the effectiveness of the employee additional income DKI Jakarta’s civil servant to performances. This study focusing on DKI Jakarta’s civil servant additional income as their income is the highest salary than other povince in Indonesia, and becoming such a masterpiece in DKI Jakarta Province. The civil servant may grateful by this situation, however people are having big expectation on employee’s performances as they have a wealthy condition. Along with the expectation growth, the researcher found it is interesting to answer people question and delineate people expectation. This study takes places on Department of Employment, Administration and Public Places in Secretariat of The Administrative City of East Jakarta. The study employed descriptive and qualitative method using the effectiveness theory of William N Dunn; efficiency, adequacy, similarity and responsivity also accuracy. It is also used the theory of performances by Wirawan; work’s results, work behavior, and personal traits. The result of research showed that employee additional income is moderately effective to raise the employee’s performances. Based on the result of interview, documentation and observation, employee additional income becoming a motivation to the employee for increasing their performances. However, the government meets some difficulty in the process of implementing the program. Although there are some problem affect the program’s effectiveness, the employee in the Department of Employment, Administration and Public Places in Secretariat of The Administrative City of East Jakarta, between staff and directions, are having mutual cooperation to solved the problem.